PERCEPTION OF RURAL CONSUMER OVER DIGITAL MARKET KARAMADAI, COMIBATORE. - DAMODHARAN, V. LAVANYA; KRISHNAMOORTHY, Dr. A. (The journal of contemporary issues in business and government, 2021)
Consumer perception plays a major role in buying behaviour. Studies show that India has more rural user internet than urban uses. Hence there is huge space for e-commerce business in rural area. The aim of the study is to understand the perception of rural consumer of digital market in karamadai - Coimbatore district. To analysis this study we have used multipliable regression technic. The result comprises of factors that encourage and discourage the rural consumers to use online shopping, we have also given few suggestions.